ANALYSIS OF THE LEARNING ENVIRONMENT IN ISLAMIC EDUCATION LEARNING AT SMAN 1 GUNUNGSARI - Ati Rahmawati; Muhamad Amier Ali; Murzal (Journal of Education, Teaching, and Learning, 2025)
This study explores the learning environment in Islamic Religious Education (IRE) at SMAN 1 Gunungsari, aiming to evaluate how various components such as infrastructure, teacher competence, curriculum, and learning resources influence the effectiveness of the learning process. The research employs a qualitative case study approach, utilizing observation, interviews, and document analysis to gather data from Islamic Education teachers and students. Key findings reveal that the integration of character education and the application of the TPACK (Technological Pedagogical Content Knowledge) framework have positively impacted the learning environment. However, challenges such as insufficient infrastructure, including a lack of comprehensive religious texts in the library and inadequate classroom facilities, remain. Despite these limitations, the learning environment fosters an interactive and engaging atmosphere, with teachers effectively utilizing available resources and integrating technology into the curriculum. The study suggests that improvements in infrastructure and teacher professional development, particularly in diversifying pedagogical approaches, are essential for further enhancing the quality of Islamic Education. These findings contribute to the ongoing effort to optimize the learning environment in Islamic Education and provide practical recommendations for future improvements.